OnDroad Planner: Building Tourist Plans Using Traveling Social Network Information - Cenamor, Isabel; de la Rosa, Tomás; Borrajo, Daniel (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
One of the key challenges in automated planning is to define the sources of information that will feed the initial state and goals of each planning task. In many domains, the information comes from company's databases. In other applications, the information is harder to obtain and it is usually partial. In this paper, we will describe an application on travel planning, where the initial state and goals will be obtained by crowdsourcing. Travel planning requires the use of plenty Internet-based resources; some of them are related to human generated opinions on all kinds of matters (e.g. hotels, places to visit, restaurants, ...). We present the OnDroad planner, a system that creates personalized tourist plans using the human generated information gathered from the minube traveling social network. OnDroad proposes an initial tourist guide according to the recommendation of the users profiles and their contacts. In addition, this guide can be continuously updated with newly generated data.